Perceptions and responses to cognitive decline in people with diabetes: A systematic review of qualitative studies - Wang, Meijuan; Guan, Xiangyun; Yan, Jingzheng; Michael, Nyagwaswa; Liu, Xueyan; Tan, Ran; Lv, Xiaoyan; Yan, Fei; Cao, Yingjuan (Frontiers in Public Health, 2023)
Objective: We aim to summarize the perceptions and responses to cognitive decline and explore performance of disease management, identify disease management deficiencies and propose strategies for improvement in people with diabetes (PWDs). Methods: A comprehensive search was performed in the following nine databases: PubMed, EMBASE, Web of Science, The Cochrane Library, PsycINFO, CINHAL, WanFang, CNKI, and VIP. The Joanna Briggs Institute (JBI) Critical Appraisal Tool for qualitative research evaluated the quality of the included studies. Descriptive texts and quotations relating to patient experience were extracted from the included studies and thematically analyzed. Results: Eight qualitative studies met the inclusion criteria from which 3 overarching themes were identified: (1)Self-perception of cognitive decline: that refers to perceived cognitive symptoms and lack of knowledge; (2)Self-response to cognitive decline: that refers to how PWDs cope with cognitive decline in their own ways; (3)External support for cognitive decline: that refers to how cognitive interventions improve disease management ability, attitudes and needs of PWDs to cognitive intervention. Conclusions: PWDs have misconceptions about their cognitive decline and suffer from them during disease management. This study may be able to provide a patient-specific reference for cognitive screening and intervention in PWDs, which could help improve disease management in PWDs with cognitive decline in clinical practice.